Vaginal leiomyoma: A case report - Dung, Tran Ngoc; Quan, Nguyen Anh (Tạp chí Nghiên cứu Y học, 2025)
Vaginal leiomyomas are rare, benign mesenchymal tumors. Since Denys de Leyden identified the first case in 1733, there have been only around 300 reported cases. This case of a surgically treated vaginal leiomyoma highlights the importance of considering this rare diagnosis in reproductive-age women. We provide a review of the relevant literature on diagnosis and management.